Ammonium lauryl sulfate-induced apoptotic cell death may be due to mitochondrial dysfunction triggered by caveolin-1. (June 2019) - Park, Eun-Jung; Seong, Eunsol; Kim, Younghoon; Lee, Kyuhong
Abstract: A recent epidemiological study suggested that chronic exposure to cleaning detergents significantly reduced lung function in consumers. In this study, we identified the toxic mechanism of ammonium lauryl sulfate (ALS), the most common detergent in consumer products, using alveolar macrophage cells. In preliminary tests, cell viability sharply decreased between 40 and 200 μg/mL, thus we determined doses of 10, 20, and 50 μg/mL for further study. When treated at a 50 μg/mL for 24 h, cell viability was 67.7 ± 3.4% of the control, and autophagosome-like vacuoles and a number of double membranes surrounding damaged mitochondria were observed in the cytosol. Intracellular ROS, the ATP amount, ER volume, acid cell compartments and mitochondrial potential rapidly reduced with dose, whereas the release of LDH and apoptotic bodies dramatically increased. Additionally, multiple cell death pathways were activated following exposure to ALS, and the expression of caveolin-1, p-Acetyl CoA carboxylase, p21, and p-ERK were greatly inhibited. Moreover, the secretion of inflammatory mediators and expression of innate- and adaptive-immune response-related proteins were remarkably reduced. Meanwhile, the secretion of TGF-β was enhanced. Therefore, we conclude that ALS-induced apoptosis may be due to mitochondrial dysfunction triggered by the inhibition of caveolin-1, and that chronic pulmonary exposure to ALS may cause adverse health effects such as cancer and fibrosis by impairing the host's pulmonary immune system. Highlights: Ammonium lauryl sulfate (ALS) is among the most common detergents in daily supplies. We identified the toxic mechanism of ALS using MH-S (alveolar macrophage cells). 24 exposure, viability rapidly decreased at a 50 μg/mL dose accompanying apoptosis. ALS induced mitochondrial dysfunction along with the inhibition of caveolin-1. Chronic pulmonary exposure to ALS may disturb the host's pulmonary immune system.